Motor imagery evokes strengthened activation in sensorimotor areas and its effective connectivity related to cognitive regions in patients with complete spinal cord injury. - Wang, Ling; Li, Xuejing; Zheng, Weimin; Chen, Xin; Chen, Qian; Hu, Yongsheng; Cao, Lei; Ren, Jian; Qin, Wen; Lu, Jie; Chen, Nan (Brain Imaging & Behavior, 2022)
The objective of this study was to investigate the alterations of brain activation and effective connectivity during motor imagery (MI) in complete spinal cord injury (CSCI) patients and to reveal a potential mechanism of MI in motor rehabilitation of CSCI patients. Fifteen CSCI patients and twenty healthy controls underwent the MI task-related fMRI scan, and the motor execution (ME) task only for healthy controls. The brain activation patterns of the two groups during MI, and CSCI patients during the MI task and healthy controls during the ME task were compared. Then the significantly changed brain activation areas in CSCI patients during the MI task were used as regions of interest for effective connectivity analysis, using a voxel-wise granger causality analysis (GCA) method. Compared with healthy controls, increased activations in left primary sensorimotor cortex and bilateral cerebellar lobules IV-VI were detected in CSCI patients during the MI task, and the activation level of these areas even equaled that of healthy controls during the ME task. Furthermore, GCA revealed decreased effective connectivity from sensorimotor related areas (primary sensorimotor cortex and cerebellar lobules IV-VI) to cognitive related areas (prefrontal cortex, precuneus, middle temporal gyrus, and inferior temporal gyrus) in CSCI patients. Our findings demonstrated that motor related brain areas can be functionally preserved and activated through MI after CSCI, it maybe the potential mechanism of MI in the motor rehabilitation of CSCI patients. In addition, Sensorimotor related brain regions have less influence on the cognitive related regions in CSCI patients during MI (The trial registration number: ChiCTR2000032793).